2014
DOI: 10.1097/iae.0b013e31829d004b
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Retinal Detachment Secondary to Macular Hole in Highly Myopic Eyes

Abstract: Combining pars plana vitrectomy with internal limiting membrane peel and silicone oil tamponade was safe and effective in treating MH-retinal detachment in highly myopic eyes. Silicone oil tamponade may improve initial anatomical success rates because of longer tamponade duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…1, 2, 3 Several approaches have been attempted such as macular buckling, scleral shortening, pars plana vitrectomy (PPV), and combinations thereof. 4, 5, 6 The macular buckling technique was the standard surgical treatment for MHRD before the introduction of PPV in 1982. 2, 7, 8, 9 The retinal attachment rate after macular buckling and scleral shortening ranged from 93.3 to 100%, although the macular hole closure rates after these procedures were unknown.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2, 3 Several approaches have been attempted such as macular buckling, scleral shortening, pars plana vitrectomy (PPV), and combinations thereof. 4, 5, 6 The macular buckling technique was the standard surgical treatment for MHRD before the introduction of PPV in 1982. 2, 7, 8, 9 The retinal attachment rate after macular buckling and scleral shortening ranged from 93.3 to 100%, although the macular hole closure rates after these procedures were unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nishimura et al reported that PPV with ILM peeling and primary silicone oil tamponade without any postoperative position restrictions led to a 92 % retinal reattachment rate after the initial surgery, with a mean duration of silicone oil tamponade of 23.3 months [ 17 ]. In another study by Meng et al [ 19 ] in 21 consecutive highly myopic eyes with RD resulting from MH, the MH closure rate was 86 % and the final retinal reattachment rate was 95.2 %. However, the occurrence of chorioretinal atrophy in patients was not reported in these studies.…”
Section: Discussionmentioning
confidence: 98%
“…Conventional approaches, including macular buckling, scleral shortening, and scleral imbrication, have been attempted to improve the surgical outcomes of eyes with MHRD [5][6][7]. With the introduction of pars plana vitrectomy (PPV) for the treatment of idiopathic MH, vitrectomy with removal of the cortical vitreous and internal limiting membrane (ILM) or gas tamponade has been widely accepted as the standard treatment for MHRD [8,9].…”
Section: Introductionmentioning
confidence: 99%